High polymorphism of the MBL2 gene in patients with atopic dermatitis. - Carréra, Matilde Campos; Moura, Patrícia; Crovella, Sergio; de Souza, Paulo Roberto Eleutério; de Alencar, Luiz Cláudio Arraes; Sarinho, Emanuel (Ann Allergy Asthma Immunol, 2010)
BACKGROUND: Low serum levels of mannose-binding lectin (MBL) are determined mainly by variant alleles of the MBL2 gene and it has been suggested that MBL may play a role in the susceptibility to atopic dermatitis (AD). OBJECTIVE: The aim was to investigate the difference of the frequency of MBL2 variant alleles in AD patients and in a group of individuals without AD, and associate the MBL2 alleles with AD severity. METHODS: MBL2 variant allele's frequency was investigated in 131 children with AD and 165 healthy children/adolescents matched by convenience. The severity of disease was graded according to the SCORing Atopic Dermatitis (SCORAD) index. The first exon variants were called "O" and the wild type "A". The variants in the promoter were H/L at -550 and X/Y at -221, determined by Real Time PCR. RESULTS: Children with AD had higher frequency of allele O and the genotypes related to low or deficient levels of MBL, when compared to the healthy group (p = 0.0012 and p < 0.001, respectively), but not with AD severity. CONCLUSION: Low or deficient MBL serum levels determined genetically may contribute to the predisposition for AD, but not for disease severity.
Keywords: Adolescent; Alleles; Child; Child, Preschool; Dermatitis, Atopic; Disease Progression; Female; Genetic Predisposition to Disease; Genotype; Humans; Infant; Male; Mannose-Binding Lectin; Polymorphism, Genetic; Promoter Regions, Genetic